PECULARITIES OF STUDENTS ’ ATTITUDE TOWARDS THE STUDIES AND THE PHYSICAL EDUCATION TEACHER IN THE ASPECT OF GENDER - Čepelionienė, Jurgita; Ivaškienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The most important factor of physical education at the university level is the teacher hence it is his qualifications, educational mastery on which depends his ability to create a favorable learning atmosphere with the respect to the educational and emotional aspects. The relationship between the physical education specialist and students, the content of the practical lessons, methods and theoretical lectures influence the formation of students’ attitude towards physical activities and the development of the practical acts The purpose of the research is to set student’s attitude towards the studies and physical education teacher relying on the gender aspect. Empirical research was conducted in the spring semester of year 2009. The 491 students were involved in this study (362 female and 129 male).